KEMAMPUAN RASIO KEUANGAN DAN CORPORATE GOVERNANCE MEMPREDIKSI PERINGKAT OBLIGASI PADA PERUSAHAAN CONSUMER GOODS - N. Agus Sunarjanto; Daniel Tulasi (Jurnal Keuangan dan Perbankan, 2013)
This study aimed to examine empirically financial ratios (leverage, liquidity, solvability, and profitability)and corporate governance for distinguishing bond rating company in investment grade and non-investmentgrade companies. The population of this research was consumer goods companies listed at Indonesia StockExchange. The research used purposive sampling, polls financial data and analysis with logistic regression.Research finding indicated that corporate governance and financial ratios were the current ratio (CR), longtermdebt ratio (LTDR), total assets and turnover (TAT), return on assets (ROA), independent commissioners(kind), managerial ownership (KM), institutional ownership and audit quality (KA) that were simultaneouslyable to predict bond rating company as investment grade companies and non investment grade companies.